'It's just a job': Understanding emotion work, de-animalization and the compartmentalization of organized animal slaughter. (May 2016) - Hamilton, Lindsay; McCabe, Darren
This article contributes to an understanding of the nexus between humans and animals by drawing on ethnographic research conducted in a British chicken factory and, more particularly, by exploring the emotional subjectivity of Meat Inspectors employed by the Food Standards Agency to oversee quality, hygiene and consumer safety within this plant. We argue that these Inspectors displayed a complex range of often contradictory emotions from the 'mechanized' to the 'humanized' and link this, in part, to the technocratic organization of factory work that compartmentalizes and sanitizes slaughter. This serves to de-animalize and commodify certain animals, which fosters an emotional detachment from them. In contrast to research which suggests that emotions switch off and on in a dialectic between violence and non-violence, or that we are living in a post-emotional society, we elucidate the co-existence, fluidity and range of emotions that surface and submerge at work. While contributing to the extant literature on 'emotionologies', we add new insights by considering how emotions play out in relation to animals.